Cytoplasmic maturation in human oocytes: an ultrastructural study † - Trebichalská, Z; Kyjovská, D; Kloudová, S; Otevřel, P; Hampl, A; Holubcová, Z (Biology of reproduction, 2021)
Female fertility relies on successful egg development. Besides chromosome segregation, complex structural and biochemical changes in the cytoplasmic compartment are necessary to confer the female gamete the capacity to undergo normal fertilization and sustain embryonic development. Despite the profound impact on egg quality, morphological bases of cytoplasmic maturation remain largely unknown. Here, we report our findings from the ultrastructural analysis of 69 unfertilized human oocytes from 34 young and healthy egg donors. By comparison of samples fixed at three consecutive developmental stages, we explored how ooplasmic architecture changes during meiotic maturation in vitro. The morphometric image analysis supported observation that the major reorganization of cytoplasm occurs before polar body extrusion. The organelles initially concentrated around prophase nucleus were repositioned toward the periphery and evenly distributed throughout the ooplasm. As maturation progressed, distinct secretory apparatus appeared to transform into cortical granules that clustered underneath the oocyte's surface. The most prominent feature was the gradual formation of heterologous complexes composed of variable elements of endoplasmic reticulum and multiple mitochondria with primitive morphology. Based on the generated image dataset, we proposed a morphological map of cytoplasmic maturation, which may serve as a reference for future comparative studies. In conclusion, this work improves our understanding of human oocyte morphology, cytoplasmic maturation, and intracellular factors defining human egg quality. Although this analysis involved spare oocytes completing development in vitro, it provides essential insight into the enigmatic process by which human egg progenitors prepare for fertilization.
Keywords: indukce ovulace; Humans; Cytoplasm; lidé; oogeneze; Oogenesis; Chromosome Segregation; cytoplazma; Oocytes; oocyty; mladý dospělý; Female; endoplazmatické retikulum; Ovulation Induction; segregace chromozomů; Mitochondria; folikuly stimulující hormon; mitochondrie; Adult; dospělí; Follicle Stimulating Hormone; Endoplasmic Reticulum; ženské pohlaví; Young Adult